2022
DOI: 10.1007/s12662-021-00794-8
|View full text |Cite
|
Sign up to set email alerts
|

Decisions and reasonings of top-class handball referees under physical load

Abstract: Correct decision-making under physical load is a central challenge for referees in sports games. Handball referees are assumed to make both a decision (calling a foul or no foul) and to call its reasonings (type of foul, punishments). However, the impact of physical load on these two aspects has not been differentiated so far. Here, in two studies, we aimed to investigate the hypothesised impact of physical load on both referees’ decisions and reasonings. To this end, N = 66 (study 1) and N = 73 (study 2) top-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Breklen et al, (2021) state that high-intensity training 3 times a week for basketball referees results in improved speed performance and reduced reaction time when making decisions on the basketball court. In turn, studies of the physical fitness of referees in handball proved that improving the results of special endurance in the training process significantly improves the efficiency of making the right decisions during the game (Blob et al, 2022). The studies conducted by us in the competitive period of football referees confirm the need to include high-intensity exercises for the development of different types of endurance in the training microcycles, but in contrast to this, the referee must have a certain reserve of strength of the muscle groups that are most involved in such work, which will enable the body to withstand such a load.…”
Section: Discussionmentioning
confidence: 99%
“…Breklen et al, (2021) state that high-intensity training 3 times a week for basketball referees results in improved speed performance and reduced reaction time when making decisions on the basketball court. In turn, studies of the physical fitness of referees in handball proved that improving the results of special endurance in the training process significantly improves the efficiency of making the right decisions during the game (Blob et al, 2022). The studies conducted by us in the competitive period of football referees confirm the need to include high-intensity exercises for the development of different types of endurance in the training microcycles, but in contrast to this, the referee must have a certain reserve of strength of the muscle groups that are most involved in such work, which will enable the body to withstand such a load.…”
Section: Discussionmentioning
confidence: 99%
“…These data are agreeing with the previous research carried out [ 27 , [30] , [31] , [32] , [33] , [34] ] and that indicated a decrease in precision at the end of the match. These results could suggest that the appearance of fatigue caused by the physical demands of the match [ 35 ] and the characteristic intensity of this type of competition, could affect the correct assessment, subject to individual cognitive abilities [ 36 ]. In fact, if to the previous statement, we add as potential stress factors the high physical stress during the matches to which the main and assistant SRs [ 37 ] are subjected and the high pressure to make decisions in front of large crowds could be explained by the previous suggestions.…”
Section: Discussionmentioning
confidence: 99%